177k views
0 votes
-4(m + 18) = 8 answer

User MCP
by
5.5k points

2 Answers

2 votes

Answer: m = -20

Step-by-step explanation:

−4(m + 18) = 8

Step 1: Simplify both sides of the equation.

−4(m + 18) = 8

(−4)(m) + (−4)(18) = 8 (Distribute)

−4m + −72 = 8

−4m − 72 = 8

Step 2: Add 72 to both sides.

−4m − 72 + 72 = 8 + 72

−4m = 80

Step 3: Divide both sides by -4.

−4m / − 4 = 80 / −4

m = −20

User Rob Grant
by
4.8k points
5 votes

Answer:

m = -20

Explanation:

first distribute:

-4(m + 18) = 8

-4m - 72 = 8

Now add 72 to both sides to get m by itself

-4m = 80

and divide by -4 on both sides

m = -20

Hope this helped! :)